The reorganisation of EU foreign relations: what role for development policies within the European institutional setup? - Sven Grimm (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
At the end of 2009 important changes will be implemented in European foreign relations. Previous reforms in European development policies have not changed the basic decision-making procedures, and the lines of responsibility for development policies have remained and will continue to remain shared by the Union and its member states. Now, however, structural issues have become imminent which affect the EU's foreign relations and for this reason will alter above all the context of its development policies. The Lisbon Agreement resulted in a major expansion of the EU's Common Foreign and Security Policy (CFSP). A Vice-President of the Commission, to be named by the Council, will in future serve as a hinge between the CFSP and other external relations, including the area of development policy. Development policies will be required to establish their relationship to the High Representative of the Union for Foreign Affairs and Security Policy . Although foreign policy and development policies in the ideal case have complementary target systems in view (e.g. long-term global security), they nevertheless work with a differentiated time horizon and from different perspectives of interest. In view of forthcoming global challenges, the retention of a strong voice in development policies at the Commission table remains decisive in importance. Otherwise the danger remains that knowledge of and competence in development policy will be lost sooner or later when development policy targets are structurally neglected or subordinated to foreign policy interests. A central decision will be made in the design of European External Action Service. A stronger structure for development policies, one which both closely meshes with the work of the de facto Foreign Minister but remains nevertheless independent, would correspond most with a consistent continuation of the EU's targets to date and would be appropriate for future challenges.
Keywords: 330